Do gifted children without specific learning disabilities read more efficiently than typically developing children? - Lesecq, Laurent; Querne, Laurent; Gornes, Julie; Buffo, Laura; Corbel, Louise; Le Moing, Anne Gaelle; Berquin, Patrick; Bourdin, Béatrice (Frontiers in Psychology, 2024)
There are no published data on the written language skills of gifted children (GC). The objective of the present study was to evaluate reading abilities of GC vs. normative data from typically developing French children (TDC). Like English, French is considered to be an opaque language.Method. GC completed the Wechsler Intelligence Scales and a battery of language tests. Only children with a score two standard deviations (SD) above the norm were included. GC with current or past academic difficulties or specific learning disorders were excluded. The GC's scores were compared with TDC's normative scores for language tests in a chi-square-test and corrected for multiple comparisons.Results. Forty-five GC were included. The highest GC's mean scores were for the WISC's Verbal Comprehension Index (VCI) and the lowest for the Processing Speed Index (from more than two SDs to one SD higher above the TDC's normative scores). GC were between 1.3 and 4.7 times more likely than TDC to achieve a high score. After correction, the distributions of the GC's and TDC's scores differed significantly with regard to spoonerism, phoneme deletion, and rapid automatic naming (p <0.001), word and sentence repetition (p ≤0.007), and the reading of meaningful text (p =0.03). GC and TDC did not differ significantly for reading meaningless texts and spelling accuracy.Discussion. As described in the literature, the GC in the present study had heterogeneous scores on the Wechsler Intelligence Scales. The GC performed better than TDC in assessments of the underlying skills of reading and when reading of meaningful texts. This advantage was lost in the absence of context, as shown by the lack of significant GC vs. TDC differences for reading meaningless texts and for spelling accuracy. Hence, GC presented a heterogeneous profile with regard to the underlying skills of reading and reading abilities. The present data should help to improve our understanding of GC's reading skills. In particular, it is now essential to determine which written language tests and which score thresholds are appropriate for identifying specific learning disorders in GC.